2012
DOI: 10.1177/0194599812446565
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Resection of Anterior Skull Base Meningiomas

Abstract: ACF meningiomas can be safely removed endonasally, offering significant advantages over the traditional transcranial approach for suitable tumors. Early audit of this approach shows results achieved by this unit are comparable with the published literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 37 publications
0
68
0
5
Order By: Relevance
“…16 Many other studies have demonstrated a wide range of CSF leak rates following resection of these lesions, as well, ranging from 9.5 to 58% with a variety of multilayered closure methods. 2,[17][18][19][20][21] Previously, autologous free grafts including fat, muscle, fascia lata, and nasal septal bone/cartilage have served as viable options for skull base reconstruction following endoscopic endonasal surgery. Kaptain et al encountered a 2.3% postoperative CSF leak rate among 257 patients with intrasellar pathologies who were reconstructed with autologous tissues after endoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…16 Many other studies have demonstrated a wide range of CSF leak rates following resection of these lesions, as well, ranging from 9.5 to 58% with a variety of multilayered closure methods. 2,[17][18][19][20][21] Previously, autologous free grafts including fat, muscle, fascia lata, and nasal septal bone/cartilage have served as viable options for skull base reconstruction following endoscopic endonasal surgery. Kaptain et al encountered a 2.3% postoperative CSF leak rate among 257 patients with intrasellar pathologies who were reconstructed with autologous tissues after endoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of the expanded endoscopic endonasal approach combined with computer tomography (CT) image guidance modalities have allowed for safe resection of orbital and anterior skull base masses. [1][2][3] However, many skull base masses require significant retraction and resection of surrounding tissues that are not ideal for endoscopic resection.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,15,21 Since the first descriptions of this technique for resection of anterior fossa meningiomas that involve the optic nerves, 11,12 tuberculum sellae meningiomas have been an attractive target: a subchiasmatic approach to a subchiasmatic lesion.However, tuberculum sellae meningiomas present a surgical excision challenge, 23 in part because of the adjacent and involved critical structures that can be placed at risk during a transcranial approach, especially the optic nerves, carotid and anterior cerebral arteries, the pituitary gland and stalk, and the hypothalamus. 24 An endoscopic endonasal approach theoretically avoids similar manipulation by approaching the meningioma through its dural base, thereby minimizing retraction of the optic nerve and decreasing the risk for postoperative visual deterioration.…”
mentioning
confidence: 99%
“…6,9,15,21 Since the first descriptions of this technique for resection of anterior fossa meningiomas that involve the optic nerves, 11,12 tuberculum sellae meningiomas have been an attractive target: a subchiasmatic approach to a subchiasmatic lesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation